Spatio-Temporal Plasma Afterglow Induces Additional Neutral Drag Force on Microparticles - van Huijstee, J. C. A.; Blom, P.; Peijnenburg, A. T. A.; Beckers, J. (Frontiers in Physics, 2022)
An emerging topic in complex plasma physics is the interaction between dust particles and afterglow plasmas. Control of plasma-particle interactions and specifically of the particle trajectories is especially relevant for plasma based contamination control applications. In systems where this contamination control is relevant, emerging or applied plasmas can be of highly transient nature, due to which contaminating particles interact with a combination of a spatial and a temporal afterglow plasma. Until now this type of plasmas and the possible interaction with embedded microparticles has remained far from fully explored in literature. In this work we visually record falling microparticles in a spatio-temporal afterglow of a low pressure inductively coupled plasma and observe a sudden and temporary reversal in their vertical velocity. Numerical simulations confirm that this effect is due to the cooling of the heated background gas in the former active plasma region, which creates a pressure wave and causes microparticles in the spatial afterglow to experience an additional neutral drag force in direction of the plasma bulk. Besides being an interesting principle phenomenon, the presence of this effect could have added value for developing plasma-driven particle contamination control applications. Moreover, for a well defined vacuum vessel geometry and plasma heating volume, this enables the use of microparticles in the spatio-temporal afterglow as probe for the neutral gas temperature in plasma.